Parasitic Helminth-Derived microRNAs and Extracellular Vesicle Cargos as Biomarkers for Helminthic Infections - Mu, Yi; McManus, Donald P.; Gordon, Catherine A.; Cai, Pengfei (Frontiers in Cellular and Infection Microbiology, 2021)
As an adaption to their complex lifecycles, helminth parasites garner a unique repertoire of genes at different developmental stages with subtle regulatory mechanisms. Parasitic worms release differential components such as microRNAs (miRNAs) and extracellular vesicles (EVs) as mediators which participate in the host-parasite interaction, immune regulation/evasion and in governing processes associated with host infection. MiRNAs are small ( 22-nucleotides) non-coding RNAs that regulate gene expression at the post-transcriptional level, and can exist in stable form in bodily fluids such as serum, plasma, and saliva. In addition to reports focusing on the identification of miRNAs or in the probing of differentially expressed miRNA profiles in different development stages/sexes or in specific tissues, a number of studies have focused on the detection of helminth-derived miRNAs in the mammalian host circulatory system as diagnostic biomarkers. Extracellular vesicles (EVs), small membrane-surrounded structures secreted by a wide variety of cell types, contain rich cargos that are important in cell-cell communication. EVs have attracted wide attention due to their unique functional relevance in host-parasite interactions and for their potential value in translational applications such as biomarker discovery. In the current review, we discuss the status and potential of helminth parasite-derived circulating miRNAs and EV cargos as novel diagnostic tools.